The impact of video feedback on motor skill and motivation in acrobatic gymnastics through the use of digital tools in physical education - Bouzid, M. S.; Melki, H.; Ben Romdhane, M.; Hammoudi, S.; Khalfallah, W.; Rezgani, Y.; Racil, G.; Padulo, J. (Journal of Human Sport & Exercise, 2025)
This study investigates the effects of video feedback (VFB) on motor learning and motivation in acrobatic gymnastics (AG), a discipline demanding high levels of coordination and spatial awareness. Forty-two non-gymnasts (aged 11.59 ± 0.70y) were assigned to either an experimental group (VFB) or a control group (verbal feedback only) and participated in an 11-session AG program over 10 weeks. The learning task involved three acrobatic figures, Airplane, Square, and Reverse handstand, performed within a choreographed sequence. Motor performance was assessed using observation grids and joint angle analysis, while motivation was measured using the situational interest scale. Results showed significantly greater improvements in the VFB group for all three figures, both in performance scores (e.g., Reverse handstand: +247% vs. +38%) and joint angles (e.g., Aeroplane: +29% vs. +8%). Moreover, students receiving VFB reported higher motivation levels. These findings underscore the pedagogical value of VFB, suggesting it enhances both technical execution and student engagement more effectively than verbal feedback alone. VFB emerges as a promising digital tool to support motor learning and motivation in physical education, particularly in complex disciplines like AG.